2016
DOI: 10.1123/japa.2015-0222
|View full text |Cite
|
Sign up to set email alerts
|

Cold Water Swimming Beneficially Modulates Insulin Sensitivity in Middle-Aged Individuals

Abstract: We determined whether cold water swimming for six consecutive months results in adaptive changes in body composition and insulin sensitivity. Thirty healthy subjects aged 50.2 ± 9.4 years were exposed to cold water at least twice a week. Body composition was determined and serum glucose and insulin served to calculate beta-cell function, insulin sensitivity, and resistance using HOMA2. Compared with control subjects, swimmers were overweight, and had greater percent body fat and beta cell function. Women had l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 0 publications
0
18
0
Order By: Relevance
“…Two main variables may explain why women can outperform men in open-water swimming: (i) the long distance of~30 km, (ii) and water colder than~20 • C. Potential explanations for the finding that women can achieve a better performance than men can be attributed to differences in anthropometric characteristics such as body composition [65], body weight [66], body fat [67][68][69][70], lean body mass [71,72], body height [73,74], muscle thickness [75] and muscle size [72]. Other possible explanations were differences in swimming biomechanics such as kinematic parameters [76], arm coordination and arm-leg coordination [76][77][78], energetic cost, differences in swimming economy and swimming efficiency [79][80][81], gliding [82], body roll [83], shoulder flexibility [84], trunk flexibility [85], knee flexibility [86,87], propelling efficiency [88].…”
Section: Potential Explanations For the Female Dominance In Long-distmentioning
confidence: 99%
“…Two main variables may explain why women can outperform men in open-water swimming: (i) the long distance of~30 km, (ii) and water colder than~20 • C. Potential explanations for the finding that women can achieve a better performance than men can be attributed to differences in anthropometric characteristics such as body composition [65], body weight [66], body fat [67][68][69][70], lean body mass [71,72], body height [73,74], muscle thickness [75] and muscle size [72]. Other possible explanations were differences in swimming biomechanics such as kinematic parameters [76], arm coordination and arm-leg coordination [76][77][78], energetic cost, differences in swimming economy and swimming efficiency [79][80][81], gliding [82], body roll [83], shoulder flexibility [84], trunk flexibility [85], knee flexibility [86,87], propelling efficiency [88].…”
Section: Potential Explanations For the Female Dominance In Long-distmentioning
confidence: 99%
“…Exposure to low temperatures can be considered a stressor, which when applied for a specific time can lead to adaptive reactions [ 6 , 23 , 24 ]. Therefore, in our study we hypothesized that cold, when applied to the entire body, may be a factor that positively modifies the aging process of bones by improving the mechanisms related to the body’s mineral balance.…”
Section: Introductionmentioning
confidence: 99%
“…Cardiovascular system Lowering blood pressure [23,47,53,54] Endocrine system Decrease in triglycerides [24,31,55] Increase in insulin sensitivity [3,11,31,56] Decrease in norepinephrine […”
Section: System Effects Referencesmentioning
confidence: 99%
“…Several studies have suggested that cold water swimming has a wide variety of health benefits [3], including changes in hematological [4] and endocrine function [5,6], fewer upper respiratory tract infections [7], amelioration of mood disorders [8] and general well-being [9]. Although chronic exposure to colder water temperatures has been shown to be beneficial to one's health, several studies have outlined the potential risks [10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%